Increasing communicative competence in two adults with Cerebral Palsy with Makey-Makey device. A case study - Calleja, Marina; Luque, María Luisa; Rodríguez, José Miguel; Liranzo, Ana (Revista de Investigación en Logopedia, 2015)
In this paper we present two cases of cerebral palsy (CP) with spastic component and severe communication difficulties as a result of a dysarthria. This dysarthria causes them a low speech intelligibility, creating important difficulties in the processes of communicative and social interaction. The aim of this study was twofold. Firstly, to check whether it was possible to turn the device known as Makey-Makey (Mk-Mk), initially conceived as an interface for video games, into a supporting device for communication of an alternative and/or augmentative communication system (CAAS) in the case of a person affected of Cerebral Palsy (CP). Secondly, to verify whether using this Mk-Mk device the participants can increase their communication skills and, specifically, if they can improve their production utterances regarding their basic needs. The results show an increase in communicative competence using a personal computer and the Mk-Mk as a device SCAA + a. The results support the suitability of using the device Mk-Mk as a SCAA + a.”
Keywords: Cerebral Palsy; Communicative competence; Communication device; Augmentative Communication System; Alternative Communication System.